ANALISIS STRUKTUR DAN NILAI TEKS SATUA I GANTI TEKEN I LACUR - Darma Minarta, I Putu Ari (Humanis; Volume 2. No. 3. Maret 2013, 2013)
Analyse about structure and assess in Text of Satua I Ganti teken I Lacur, to comprehend the structure elements and assess. Basis for theory used in this analysis structural theory and the theory of assess. Structural theory used the theory of Teeuw that is dominant elements in belleslettres. To analyse the value it used the value theory submitted by Yudibrata, value is policy storey;level, kindliness, and usefulness owned by something. The value maybe alighted from a somebody perception of concerning humanity, certifiable, and glory. Method used in this analysis is divided] into three phase that is, ready of data with the method read the, processing and analyse the data with the analytic descriptive method, and presentation result of data analysis by using informal method   Result obtained in this analysis is expressing of narrative structure develop;building Text of Satua I Ganti Teken I Lacur covering: incident, groove the, background, figure and figure, theme, and commendation. Others analyse this also express the values which is consisted in the Text of Satua I Ganti Teken I Lacur covering: value karmaphala, social value, and assess esthetics
Keywords: Satua, Structure, and Assess.